Classification of Clinical Isolates of Klebsiella pneumoniae Based on Their in vitro Biofilm Forming Capabilities and Elucidation of the Biofilm Matrix Chemistry With Special Reference to the Protein Content - Singh, Ashish Kumar; Yadav, Shivangi; Chauhan, Brijesh Singh; Nandy, Nabarun; Singh, Rajan; Neogi, Kaushik; Roy, Jagat Kumar; Srikrishna, Saripella; Singh, Rakesh Kumar; Prakash, Pradyot (Frontiers in Microbiology, 2019)
Klebsiella pneumoniae is a human pathogen, capable of forming biofilms on abiotic and biotic surfaces. The limitations of the therapeutic options against Klebsiella pneumoniae is actually due to its innate capabilities to form biofilm and harbouring determinants of multidrug resistance. We utilized a newer approach for classification of biofilm producing Klebsiella pneumoniae isolates and subsequently we evaluated the chemistry of its slime, more accurately its biofilm. We extracted and determined the amount of polysaccharides and proteins from representative bacterial biofilms. The spatial distribution of sugars and proteins were then investigated in the biofilm matrix using confocal laser scanning microscopy (CLSM). Thereafter, the extracted matrix components were subjected to sophisticated analysis incorporating Fourier transform infrared (FTIR) spectroscopy, Nuclear magnetic resonance (NMR) spectroscopy, one-dimensional gel-based electrophoresis (SDS-PAGE), High-performance liquid chromatography (HPLC) and MALDI MS/MS analysis. Besides, the quantification of its total proteins, total sugars, uronates, total acetyl content was also done. Results suggest sugars are not the only/ major constituent of its biofilms. The proteins were harvested and subjected to SDS-PAGE which revealed various common and unique protein bands. The common band was excised and analyzed by HPLC. MALDI MS/MS results of this common protein band indicated the presence of different proteins within the biofilm. The 55 different proteins were identified including both cytosolic and membrane proteins. About 22 proteins were related to protein synthesis and processing while 15 proteins were identified related to virulence. Similarly, proteins related to energy and metabolism were 8 and those related to capsule and cell wall synthesis were 4. These results will improve our understanding of Klebsiella biofilm composition and will further help us design better strategies for controlling its biofilm such as techniques focused on weakening/targeting certain portions of the slime which is the most common building block of the biofilm matrix.